2016
DOI: 10.1097/mol.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis

Abstract: In this review, we will summarize the latest findings on the interactions between lipids and the immune system, and we will discuss the potential consequences of these novel insights for future therapies for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
103
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(112 citation statements)
references
References 76 publications
2
103
0
7
Order By: Relevance
“…Visvikis et al recently identified that HLH-30 and its mammalian homolog TFEB is a key transcriptional regulator of the early innate immune response involving antimicrobials and cytoprotective responses (Visvikis et al, 2014). Interestingly, lipoprotein metabolism and the innate immune systems are increasingly recognized as being functionally linked (Schaftenaar et al, 2016). Although not demonstrated in C. elegans, in higher organisms lipoproteins have been shown to be capable of protecting against lipopolysaccharide (LPS)-induced toxicity through their ability to bind LPSs, thereby modulating the overall host response to this bacterial toxin (Barcia and Harris, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Visvikis et al recently identified that HLH-30 and its mammalian homolog TFEB is a key transcriptional regulator of the early innate immune response involving antimicrobials and cytoprotective responses (Visvikis et al, 2014). Interestingly, lipoprotein metabolism and the innate immune systems are increasingly recognized as being functionally linked (Schaftenaar et al, 2016). Although not demonstrated in C. elegans, in higher organisms lipoproteins have been shown to be capable of protecting against lipopolysaccharide (LPS)-induced toxicity through their ability to bind LPSs, thereby modulating the overall host response to this bacterial toxin (Barcia and Harris, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia, a major MetS feature, induces inflammation and plays a fundamental role in atherosclerosis development [ 19 ]. This dyslipidemia is also associated with structural modifications in the native LDL that are currently recognized as a prerequisite for the initiation of lipid accumulation in the arterial intima [ 45 ].…”
Section: Lrp1 In the Metabolic Syndromementioning
confidence: 99%
“…In glucose homeostasis, LRP1 has a regulatory action on the insulin receptor (IR) and GLUT4 activation [ 10 , 16 , 18 ], which has been strongly associated with insulin resistance developed during MetS. In addition, inflammatory processes induced during MetS are also involved in the development of atherosclerosis [ 19 ]. In this case, LRP1 is a molecular and cellular mediator for M2 to M1 macrophage transformation and production of proinflammatory factors that occur in the development of atherosclerotic lesions [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a growing body of evidence suggests that the pathogenesis of atherosclerosis is much more complex than formerly believed. Immune cells and inflammation play a key role in its pathogenesis in conjunction with hyperlipidemia (4). However, how lipids interact with the immune system is largely unknown.…”
mentioning
confidence: 99%